NILAI-NILAI MORAL DALAM DONGENG PUTRI BERKULIT KUNING KARYA MADE TARO - Ni Luh Ayu Catri; Ketut Yarsama (LP3M Universitas PGRI Mahadewa Indonesia, 2024)
Fairy tales are fun for children, and can optimize children's character development in achieving thinking development. Intellectual intelligence can be fulfilled if parents are able to take the time to tell stories to their children. This research discusses the moral values contained in the fairy tale